The Effect of Pozzolans and Mineral Wastes on Alkali-silica Reaction in Recycled Aggregated Mortar - Külekçi, Gökhan (Periodica Polytechnica Civil Engineering, 2021)
In this study, it was aimed to examine recycled aggregates (RA), which are considered as aggregates, in terms of alkali-silica reaction (ASR) before being used in concrete, to determine the risk status and to reduce the ASR value. In order to reduce and stop the ASR, the cement was replaced with clay brick and fly-ash by 10–40 %. Marble waste and Pb-Zn mine waste were used instead of RA in order to reduce aggregate reactivity. At the end of 28 days, compared to the control sample, it was observed that mortar bar samples containing tailings instead of fine RA has 18 % less expansion and marble waste (MW) added samples again instead of fine RA has 34 % less expansion. Furthermore, 40 % fly ash (FA) added samples decreased the level of ASR for 96 %, and in 10 % clay brick mixed samples ASR formation is decreased to 85 %. As a result, recycled aggregates were determined to be reactive for ASR. It has been determined that marble and lead-zinc mine facility wastes added as replace with to RA reduce the expansion effect by ASR in the cement paste. With this study, it has contributed to the safe use of the increasing use of RA in the world.